About the lexical-semantic features of anthroponyms - Alimova Zarifaxon Vaxobovna; Jorayeva Rohatoy Rahmatjon qizi (Zien Journals, 2022)
This article is about the study of anthroponyms, which are lexical units in world and Uzbek linguistics, their lexical-semantic structure, which is one of the important features of the lexical richness of the language. Famous noun and their meanings are also explained, and the use of personal names in positive or negative places is explained
Keywords: Anthroponyms; famous nouns; personal nouns; lexical meaning